Post a New Question

calculus

posted by .

lim (x^(2)-4)/(x-2)
x->2

lim
x->1 (x+1)/(x-1)

  • calculus -

    ( x ^ 2 - 4 ) / ( x - 2 ) =

    ( x + 2 ) * ( x - 2 ) / ( x - 2 ) =

    x + 2

    lim ( x ^ 2 - 4 ) / ( x - 2 ) as x->2 =

    lim ( x + 2 ) as x->2 = 2 + 2 = 4


    ( x + 1 )/ ( x - 1 ) = 2 / ( x - 1 ) + 1

    lim ( x + 1 )/ ( x - 1 ) as x->1 =

    lim [ 2 / ( x - 1 ) + 1 ] as x->1 = + OR - infinitty

    becouse lim 2 / ( x - 1 ) as x->1 = + OR - infinity

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question